THE EFFECT OF SUPPLEMENTED CELLULOLYTIC BACTERIA B-6 AS A PROBIOTIC SOURCHES IN DRINKING WATER ON THE PROTEIN, FAT, CHOLESTEROL AND EGG YOLK COLOR CONTENTS IN EGG OF LOHMANN BROWN LAYING HENS AGED 40-48 WEEK - I. B. P. O., Dananjaya; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
The aim of this research is to study the effect of supplemented cellulolytic bacteria B-6 as a probiotic sourches in drinking water on the protein, fat, cholesterol and egg yolk color contents in egg of Lohmann Brown laying hens aged 40-48 week. The research was conducted in Dajan Peken Village, Tabanan, Bali, for three months. The design used in this study was Completely Randomized Design with three treatments and six replications. The treatments were: drinking water without probiotic addition of B-6 Cellulolytic bacteria as control (A), drinking water with probiotics of B-6 Cellulolytic bacteria as much as 0,2% (B), and drinking water with probiotic of B-6 Cellulolytic bacteria with 0,4% (C). The variables observed in this study were egg yolk protein, fat, cholesterol and egg yolk color. The results showed that the egg yolk protein and egg yolk color at treatment of B and C were significantly higher (P<0,05) than those of A treatment, while egg yolk fat and egg yolk cholesterol at treatment of B and C were significantly lower (P<0,05) than those of A treatment. It can be concluded that the supplemented of 0,2% and 0,4% cellulolytics bacteria B-6 as a probiotic sourches in drinking water improvement yolk color and protein content of egg, but decreasing fat and cholesterol content in egg of Lohmann Brown laying hens. Key Words : Cellulolytic Bacteria B-6 , Lohmann Brown, Egg yolk